Enhanced Electrochemical Performance of Li2FeSiO4/C Positive Electrodes for Lithium-Ion Batteries via Yttrium Doping. (10th January 2016) - Qiu, Hailong; Yue, Huijuan; Zhang, Tong; Ju, Yanming; Zhang, Yongquan; Guo, Zhendong; Wang, Chunzhong; Chen, Gang; Wei, Yingjin; Zhang, Dong
Highlights: Yttrium doped Li2 FeSiO4 /C are successfully fabricated via a sol-gel method. The Yttrium doping improves the electronic conductivity and lithium ion diffusion coefficient. Li2 Fe0.98 Y0.02 SiO4 /C exhibits the best rate capability and cycle stability. Abstract: Y-doped Li2 Fe1−x Yx SiO4 /C (x = 0, 0.02, 0.04) composites are successfully synthesized via a sol-gel method. X-ray diffraction, field emission scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, Raman spectrometry and UV-visible spectroscopy are used to investigate the effect of yttrium doping on the characteristics of Li2 FeSiO4 /C. The results show that yttrium (Y) does enter the crystal structure of Li2 FeSiO4 and negligibly affect the morphology of the composites as well as the structural properties of the coated carbon. The electrochemical performance is evaluated by galvanostatic charge-discharge and electrochemical impedance spectra. Li2 Fe0.98 Y0.02 SiO4 /C exhibits the best rate capability and cycle stability among the three samples. The enhanced electrochemical performance is attributed to its enhanced electronic conductivity, higher lithium ion diffusion coefficient and better structure stability due to the proper amount of Y doping in Fe sites.